2010
DOI: 10.1007/s12185-010-0735-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of bacterial infection in multiple myeloma patients with VAD regimen without intermittent high-dose dexamethasone

Abstract: Vincristine-adriamycin-dexamethasone (VAD) regimen with intermittent high-dose dexamethasone (HD) has been used as primary chemotherapy for multiple myeloma (MM) patients who are candidates for high-dose therapy or present with renal failure. However, dexamethasone increases the risk of infection in MM patients. We retrospectively evaluated treatment efficacy and infectious events in MM patients undergoing VAD with or without HD. Seventy-seven consecutive patients who received VAD without HD (n = 37) or VAD-HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…No difference in infection rate was found between different ISS groups of patients, but advanced Durie-Salmon Stage IIIB 3B was significantly associated with more frequent infective complications. Contrary to some other studies [ 43 , 44 ], this result supports the idea that large tumour burden, especially when associated with renal failure, is an important infection risk factor in myeloma patients [ 43 , 44 ]. Like in other groups, a positive correlation between renal dysfunction and infections was found and these patients had a significantly higher rate of infective complications [ 10 , 43 , 45 , 46 , 47 , 48 , 49 ], which should be included in the estimation of infection risk [ 10 , 43 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 83%
“…No difference in infection rate was found between different ISS groups of patients, but advanced Durie-Salmon Stage IIIB 3B was significantly associated with more frequent infective complications. Contrary to some other studies [ 43 , 44 ], this result supports the idea that large tumour burden, especially when associated with renal failure, is an important infection risk factor in myeloma patients [ 43 , 44 ]. Like in other groups, a positive correlation between renal dysfunction and infections was found and these patients had a significantly higher rate of infective complications [ 10 , 43 , 45 , 46 , 47 , 48 , 49 ], which should be included in the estimation of infection risk [ 10 , 43 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 83%
“…In an unselected cohort, Caravita et al [ 45 ] reported that only ISS stage was a risk factor affecting severe infection development. Isoda et al [ 46 ] indicated that advanced ISS stage was an independent risk factor associated with severe (grade C 3) bacterial infection in MM patients. A large number of studies [ 13 , 26 , 33 ] have shown that advanced ISS stage is an important risk factor for infection in MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In an unselected cohort, Caravita et al [45] reported that only ISS stage was a risk factor affecting severe infection development. Isoda et al [46] indicated that advanced ISS stage was an independent risk factor associated with severe (grade C 3) bacterial infection in MM patients. A large number of studies [13,26,33] have shown that advanced ISS stage is an important risk factor for infection in MM patients.…”
Section: Discussionmentioning
confidence: 99%